Fruit Ripening Regulation of α-Mannosidase Expression by the MADS Box Transcription Factor RIPENING INHIBITOR and Ethylene - Irfan, Mohammad; Ghosh, Sumit; Meli, Vijaykumar S.; Kumar, Anil; Kumar, Vinay; Chakraborty, Niranjan; Chakraborty, Subhra; Datta, Asis (Frontiers in Plant Science, 2016)
α-Mannosidase (α-Man), a fruit ripening-specific N-glycan processing enzyme, is involved in ripening-associated fruit softening process. However, the regulation of fruit-ripening specific expression of α-Man is not well understood. We have identified and functionally characterized the promoter of tomato (Solanum lycopersicum) α-Man to provide molecular insights into its transcriptional regulation during fruit ripening. Fruit ripening-specific activation of the α-Man promoter was revealed by analysing promoter driven expression of beta-glucuronidase (GUS) reporter in transgenic tomato. We found that RIPENING INHIBITOR (RIN), a MADS box family transcription factor acts as positive transcriptional regulator of α-Man during fruit ripening. RIN directly bound to the α-Man promoter sequence and promoter activation/α-Man expression was compromised in rin mutant fruit. Deletion analysis revealed that a promoter fragment (567 bp upstream of translational start site) that contained three CArG boxes (binding sites for RIN) was sufficient to drive GUS expression in fruits. In addition, α-Man expression was down-regulated in fruits of Nr mutant which is impaired in ethylene perception and promoter activation/α-Man expression was induced in wild type following treatment with a precursor of ethylene biosynthesis, 1-aminocyclopropane-1-carboxylic acid (ACC). Although, α-Man expression was induced in rin mutant after ACC treatment, the transcript level was less as compared to ACC-treated wild type. Taken together, these results suggest RIN-mediated direct transcriptional regulation of α-Man during fruit ripening and ethylene may acts in RIN-dependent and -independent ways to regulate α-Man expression.